Penguatan Kemampuan Guru-Guru di Kecamatan Kaliwungu dalam Membuat Media Pembelajaran Berbasis Artificial Intelligence - Aries Tika Damayani; Kartinah Kartinah; Choirul Huda; F X Didik Purwosetiyono (Pelita: Jurnal Pengabdian kepada Masyarakat, 2026)
In this era of the 5.0 industrial revolution and the rapid advancement of information technology, today's students are a digital generation accustomed to visual and interactive stimulation. Traditional teaching methods that rely solely on lectures are no longer adequate to foster student interest, both at the elementary and secondary levels. The purpose of this community service is to introduce the existence of Artificial Intelligence and assist teachers in utilizing Artificial Intelligence in creating learning media in the classroom. The method used is an interactive workshop method that focuses on direct practice in addition to providing material and emphasizing the sustainability of this activity. The results of this activity are 80% of participants from teachers in the Piere Tendean Cluster in Kendal Regency are able to create learning media based on Artificial Intelligence. Based on what happened during the workshop and the quite positive results, it can be concluded that similar activities can be repeated in other Clusters with a wider variety of Artificial Intelligence-based learning media.